Effect of topographic and temporal (maturity) gradients on the nutritive quality of semiarid herbaceous communities - Perez-Corona, M E; García-Criado, B; Vazquez de Aldana, B R; Garcia-Ciudad, A (Communications in Soil Science and Plant Analysis, 1994)
Abstract Five slopes representative of the ?dehesa?; grassland communities in the semi?arid zones of Central?Western Spain (province of Salamanca) were studied. Above?ground biomass production was recorded from April to June and the NDF (neutral detergent fibre), ADF (acid detergent fibre), hemicellulose, cellulose, lignin, and digestibility were determined in the dry matter. Principal component analysis was applied to the data. The changes with time along the growth period show a parallel effect on the three positions of the slope, although the effect tended to be greater on the middle and upper zones. There were decreases in the levels of protein, cellular content, and digestibility, and an increase in cell wall components. The variability in nutritive characteristics induced by the phenology and time changes in the communities was reflected in the first factor of analysis, whereas the topographic gradient was related to the second component.
doi: 10.1080/00103629409369171
Keywords: dehesa grasslands; digestibility (PG); Nutritive quality; Semi-arid areas